Hybrid Education Program for Couples: A Strategy to Enhance Pregnancy Quality of Life - Sri Widatiningsih; Mundarti Mundarti; Esti Handayani; Christin Hiyana Tungga Dewi (Jurnal Kesehatan Vokasional, 2025)
Background: Pregnancy involved physical, emotional, and social changes, making spousal support crucial in reducing stress, anxiety, and improving maternal quality of life. However, participation of mothers and husbands in prenatal classes in Indonesia remained low. A hybrid education model (online and face-to-face) had the potential to address these limitations.Objective: This study aimed to assess the effectiveness of a digital-based hybrid companion class on improving the quality of life of pregnant women in Magelang City.Methods: This was a quasi-experimental study with a non-randomized pretest-posttest with control group design. The sample consisted of 60 couples of reproductive age (30 intervention, 30 control) selected through simple random sampling. The hybrid class intervention included modules, educational videos, and mentoring through WhatsApp, conducted in four sessions. Quality of life was measured using WHOQOL-BREF at three time points and analyzed with GLM-RM.Results: The intervention significantly improved the quality of life of pregnant women in the psychological domain (p = 0.001; η² = 69.3%), social domain (p = 0.021; η² = 34.2%), and environmental domain (p = 0.001; η² = 65.7%), while the physical domain was not significant (p = 0.510).Conclusion: The digital-based hybrid companion class was effective in improving the quality of life of pregnant women in psychological, social, and environmental aspects. Integration of the program into antenatal services was recommended to enhance the role of husbands in pregnancy care.